The Incidence of Tuberculous Cervical Lymphadenitis- Three Year Study of Sixty Cases (Bangladesh Medical Journal, 2014)
Tuberculous cervical lymphadenitis (TCL) is not very uncommon in our country. A series of 60 cases was studied from 204 non- thyroid neck swelling which were selected from 20,558 patients attending in ENT department in Central Police Hospital and Mitford Hospital, Dhaka in 3 years. The incidence of TCL was 29.41% among the non- thyroid neck swelling and 0.3% from total number of patients attending in ENT department. The most vulnerable ago group was the second decade 38.33% with female preponderance ( Female male ratio was 2: 1). The common presentaions were neck swelling (100%), fever (66.67%), night sweat (50%). 50% cases were associated with pulmonary tuberculosis. Tuberculin test was positive in 73.34%. Maximum number of patients were from low socioeconomic class and BCG vaccination had a significant protective role (31.67% were vaccinated and 68.33% were one- vaccinated). On histopathology of cervical lymph nodes caseation necrosis was found in 85% of cases.DOI: http://dx.doi.org/10.3329/bmj.v41i2.18793 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 9-12